Modelling partial customer churn in the Portuguese fixed telecommunications industry by using survival models - Portela, Sofia Lopes (2013)
Considering that profits from customer relationships are the lifeblood of firms (Grant and Schlesinger, 1995), an improvement on the customer management is essential to ensure the competitivity and success of firms. For the last decade, Portuguese customers of fixed telecommunications industry have easily switched the service provider, which has been very damaging for the business performance and, therefore, for the economy. The main objective of this study is to analyse the partial churn of residential customers in the fixed-telecommunications industry (fixed-telephone and ADSL), by using survival models. Additionally, we intend to test the assumption of constant customer retention rate over time and across customers. Lastly, the effect of satisfaction on partial customer churn is analysed. The models are developed by using large-scale data from an internal database of a Portuguese fixed telecommunications company. The models are estimated with a large number of covariates, which includes customer’s basic information, demographics, churn flag, customer historical information about usage, billing, subscription, credit, and other. Our results show that the variables that influence the partial customer churn are the service usage, mean overall revenues, current debts, the number of overdue bills, payment method, equipment renting, the existence of flat plans and the province of the customer. Portability also affects the probability of churn in fixed-telephone contracts. The results also suggest that the customer retention rate is neither constant over time nor across customers, for both types of contracts. Lastly, it seems that satisfaction does not influence the cancellation of both types of contracts.